Factors contributing to morning rain in the upper Río Chagres Basin, Panamá - Ishizaki, Noriko N.; Nakaegawa, Tosiyuki; Pinzón, Reinhardt; Sasaki, Hidetaka (Frontiers in Earth Science, 2023)
The Upper Chagres River Basin plays an important role in the stable operation of the Panama Canal. Previous studies have shown that there is a salient regional difference in the diurnal variation of precipitation in the basin. Precipitation during the rainy season peaks in the early afternoon throughout the basin, but precipitation is also observed in the morning at sites in the northern part of the basin. However, the cause of this is not clear due to limited ground observation. To address this issue, we conducted dynamical downscaling experiments with a horizontal grid spacing of 5 and 2 km and nested in a global atmospheric model with horizontal grid spacing of approximately 20 km. The results showed that the 2 km convection-permitting model successfully reproduced regional differences in observed diurnal variations. The downscaled results indicated that intensified low-level northeasterly winds over the southern Caribbean Sea triggered favorable conditions for morning rain with an orographic effect under the seaside coastal regime in the western Caribbean Sea. This is in contrast to precipitation peaks in the early afternoon under a landside coastal regime.